The determinants of Covid-19 mortality rates across Europe: Assessing the role of demographic and socioeconomic factors during the first wave of the pandemic - Psycharis, Yannis; Tsimbos, Cleon; Verropoulou, Georgia; Doukissas, Leonidas (REGION, 2021)
The aim of this paper is to examine empirically the impact of the demographic structure and socio-economic environment on the Covid-19 mortality rate across 29 European countries. The analysis is based on empirical data recorded cumulatively from the start of the Covid-19 disease until 26th May 2020 covering ‘the first wave of the pandemic’. Results indicate that, although countries with a higher degree of ageing structure are anticipated to be more vulnerable to Covid-19, this study provides evidence that population ageing contributes only marginally to Covid-19 death rates across Europe. Urbanization, the level of economic development and health care systems, seem to better explain patterns of interstate mortality rates. The analysis provides important policy implications since it underlines the importance of urbanization and socio-economic conditions in the accelerating incidence of casualties and signifies the importance of health care systems for the protection of people and places from the pandemic.